3D Sustainability Analysis of Integrated Process Design and Control for Production of Cyclohexanone - Siti Aminah, Zakaria; Mohd Jufri, Zakaria; Mohamad Rizza, Othman; Mohd Kamaruddin, Abd Hamid (2014)
The objective of this paper is to highlight the use of a three-dimensional (3D) sustainability index in performing a sustainable integrated process design and control (Sustain-IPDC) for a reactor system. Sustain-IPDC for reactor systems is formulated as a mathematical programming problem and solved by decomposing it into six sequential hierarchical sub-problems: (i) pre-analysis, (ii) design analysis, (iii) controller design analysis, (iv) sustainability analysis, (v) detailed economic analysis,and (vi) final selection and verification. By using thermodynamics and process insights, a bounded search space is first identified. Then, the feasible solution space is further reduced to satisfy the process design, controller design, sustainability constraint and economical in stage 2, 3, 4 and 5 respectively. Lastly, all the feasible candidates are ordered according to the defined performance criteria. In this methodology, the concept of an attainable region (AR) diagram is used in finding the feasible candidates. The targets for this optimal solution is defined and selected at the maximum point of the AR diagram. Then, the proposed methodology is applied to the production of cyclohexanone by using a continuous-stirred tank reactor (CSTR) system. The results show that the proposed methodology is capable in finding an optimal solution for a CSTR design problem that satisfy design,control, sustainability and economic criteria in an easy and systematic manner.